Identification of fungi extracted from tortillas from different corn races (Zea mays L.) - López-Morales, Fernando; Aragón-García, Agustín; Pérez-Torres, Betzabeth Cecilia; Vásquez-Carrillo, Gricelda; Castillo-Hernández, Dalia; Aragón Sánchez, Miguel (Ecosistemas y Recursos Agropecuarios, 2023)
The objective was to identify the strains, quantity and diversity of fungi present in tortillas of 14 corn breeds. The weight of the fungal complex (PCH) was determined and the identification of its fungi and characteristics of the grain (flotation index), nixtamal (nixtamal moisture and dough moisture) and tortilla (tortilla moisture at 24 and 48 hours). An analysis of variance was performed on the data. All variables presented significant differences (p ≤ 0.05). For the PCH the highest statistically different averages were the Naltel de altura breed (0.69 g) and Arrocillos amarillo breed (0.68 g) per tortilla. The Chalqueño breed had the highest number of mushrooms in the complex (Aspergillus flavus, Mucor sp., Penicillium sp., Rhizopus oryzae, Acremonium sp. y Alternaria sp.) unlike the fungus Penicillium sp., the Conico breed was the second best and in Pepitilla only the Acremonium sp. fungus was identified. For the humidity of nixtamal and dough moisture, the Pepitilla breed obtained the best values with 49.7 and 60.9%, respectively. There were differences of 65.2% in the PCH between the races evaluated, with the highest and lowest weight being the tall Naltel and Chalqueño breeds, respectively.